Dynamic and Modal Responses of the Grouted Multiple Strands Stay-Cables of the Bill Emerson Memorial Bridge - Xiangwen, Zuo (Université d'Ottawa / University of Ottawa, 2015)
Cable-stayed bridges are massive structures which rely on all their structural components for achieving the structural stability. Usually bridge stay-cables are the most flexible elements of the cable-stayed bridge structures, thus continuous efforts are made for improving their performance under different loadings. A new technology of constructing and installing the inclined bridge stay-cables, involves using internal strands grouted together in a cement paste or in a polymer gel material; such method has the advantage of allowing replacing of rusted strands individually, without affecting the functionality of the entire bridge stay-cable. However, recent studies have reported a change in natural vibrations of such inclined cables used for the construction of cable-stayed bridges. The current research aims at clarifying the dynamic properties of the internal strands in the cable, under the influence of the grout surrounding material and the interaction with the other inner strands under different wind loading scenarios. The effectiveness of the crossties in mitigating the wind-induced vibration has also been studied. A finite element model was developed using the nonlinear analysis through the Abaqus commercial software. Some assumptions were made for modelling the stay-cables of the Bill Emerson Memorial Bridge, and to simulate the inner strands and the grout interaction. Both modal and time-history analyses were carried out on the stay-cables fan which connects the tower to the main span deck of the Bill Emerson Memorial Cable-stayed Bridge. The natural frequencies and the vibration mode shapes of a single cable, or group of cables respecting the arrangement of the inclined cables of the bridge has been determined, as well as the displacements under the field wind loads at different points in the stay-cables network. The results show how the behaviour of the cables differs from the previous research on the stay-cable which employed only a simplified beam element as one uniform property of the cable. Several comparisons haven been made between the results obtained in the current study and outcomes reported in the existing literature; the effectiveness of the crossties has been partly verified. Also the results of the modal analysis were compared with the site measurements performed for the Bill Emerson Memorial Bridge and relatively good agreement was found for the natural frequencies and the mode shapes of the inclined stay cables.